2023
DOI: 10.1021/acsomega.2c06897
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized Control of Acidity in Multiplexed Microreactors

Abstract: The control of acidity drives the assembly of biopolymers that are essential for a wide range of applications. Its miniaturization can increase the speed and the possibilities of combinatorial throughput for their manipulation, similar to the way that the miniaturization of transistors allows logical operations in microelectronics with a high throughput. Here, we present a device containing multiplexed microreactors, each one enabling independent electrochemical control of acidity in ∼2.5 nL volumes, with a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…This electronic control allows for greater quantitative control over the pH and EGA is here utilised to induce a change in pH over time on a printed circuit board (PCB) platform with the aim of producing a micro uidic Labon-PCB device to quantitatively control pH to preconcentrate proteins within a sample for the rst time. Building on our previously published work 13 , this work utilised a commercially produced PCB array to achieve protein preconcentration of two case study proteins, bovine haemoglobin (bHb) and green uorescent protein (eGFP), using optical and electrochemical methods to control and monitor the pH local to an array of individually addressed electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…This electronic control allows for greater quantitative control over the pH and EGA is here utilised to induce a change in pH over time on a printed circuit board (PCB) platform with the aim of producing a micro uidic Labon-PCB device to quantitatively control pH to preconcentrate proteins within a sample for the rst time. Building on our previously published work 13 , this work utilised a commercially produced PCB array to achieve protein preconcentration of two case study proteins, bovine haemoglobin (bHb) and green uorescent protein (eGFP), using optical and electrochemical methods to control and monitor the pH local to an array of individually addressed electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…For peptide synthesis, however, conditions are more demanding than for nucleotide synthesis, i.e., acidic conditions required for stepwise deprotection cycles are more extreme, and possible side reactions of amino acid side chains must be averted. We recently described an improved reactor concept for electrochemical acid production, and demonstrated that it affords good yields in the local deprotection of acid-labile groups in organic electrolytes compatible with peptide synthesis [13][14][15]. To achieve high-density microarrays, these electrochemical reactors can be miniaturized and integrated with MOS circuits.…”
Section: Introductionmentioning
confidence: 99%